Capacity building in construction health and safety research, education, and practice in Pakistan. Issue 1 (1st February 2016) - Azhar, Salman; Choudhry, Rafiq M.
Abstract : Purpose: – The purpose of this paper is to present findings of a capacity building project on construction health and safety that is recently completed in Pakistan. The major objectives of this project are: first, to benchmark the current state of construction health and safety practices in Pakistan and to identify the data needs for continuous performance measurement; second, to develop health and safety guidelines; third, to develop adequate educational and training material; and finally, to improve the existing regulatory infrastructure for worker health and safety. Design/methodology/approach: – Mixed-methods approach is adopted for data collection which included site observations, surveys, semi-structured interviews, and case studies. The methodology consists of following major tasks: first, literature review and study of best practices; second, investigation of existing safety practices and development of guidelines; third, educational and training programs for construction professionals and educators; and finally, development of a strategic framework for continuous improvement in construction safety culture, laws, and practices. Collected data were analyzed using various qualitative and quantitative data analysis methods. Findings: – The enforcement of health and safety regulations on construction sites is very limited in Pakistan. Procedures for formulating, implementing, and monitoring safety rules and regulations are weak, and the implementation of safety management systems does not occur on most construction sites. The paper presents a detailed plan to improve the health and safety culture, laws, and practices in Pakistan. Practical/implications: – Detailed proposals for improving existing construction health and safety laws and regulations are prepared for relevant regulatory and statutory bodies and ministries in Pakistan. From an educational perspective, comprehensive health and safety training material are developed and training workshops are conducted in major cities of Pakistan. Over 1, 000 construction professionals benefited from these workshops. Social/implications: – The project helped in raising awareness about construction health and safety in Pakistan. Originality/value: – The project benchmarked existing health and safety practices in Pakistan. It identified data needs for continuous monitoring of health and safety performance and provided a mechanism for collecting such data. The project produced international standard health and safety training material that can fulfill the local needs. The project deliverables are extremely helpful for other developing countries in the region.